2021
DOI: 10.2147/ott.s294993
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutation Burden and Differentially Mutated Genes Among Immune Phenotypes in Patients with Lung Adenocarcinoma

Abstract: Introduction Nowadays, immune checkpoint blockades (ICBs) have been extensively applied in non-small cell lung cancer (NSCLC) treatment. However, the outcome of anti-program death-1/program death ligand-1 (anti-PD-1/PD-L1) therapy is not satisfying in EGFR -mutant lung adenocarcinoma (LUAD) patients and its exact mechanisms have not been fully understood. Since tumor mutation burden (TMB) and tumor immune phenotype had been thought as potential predictors for efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…It has also been studied in EGFR-mutated NSCLC patients [ 42 ]. When patients with ADC were segmented into low-level (TMB < 10) and high-level (TMB ≥ 10) groups according to TMB, patients without EGFR mutation tended to have a higher level of TMB (OR = 4.707) [ 43 ]. Further, in the analysis of different EGFR mutation types, they found patients with 19-Del, L858R, and uncommon mutations had comparable TMB levels ( p = 0.611).…”
Section: Pathological Featuresmentioning
confidence: 99%
“…It has also been studied in EGFR-mutated NSCLC patients [ 42 ]. When patients with ADC were segmented into low-level (TMB < 10) and high-level (TMB ≥ 10) groups according to TMB, patients without EGFR mutation tended to have a higher level of TMB (OR = 4.707) [ 43 ]. Further, in the analysis of different EGFR mutation types, they found patients with 19-Del, L858R, and uncommon mutations had comparable TMB levels ( p = 0.611).…”
Section: Pathological Featuresmentioning
confidence: 99%
“…NTRK3 mutation is associated with enhancing immunity and immunogenicity in patients with lung adenocarcinoma (LUAD) and can predict a good prognosis in LUAD patients treated with ICIs ( 48 ). Among LUAD, PTEN mutation is often associated with the immune microenvironment and expresses differently in different TMB ( 49 ). NSD3 is a crucial regulator of LUSC and a potential driving factor in lung cancer with FGFR1 amplification ( 50 ), which may be a potential target for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the definition of mutation sites in the synchronous multiple primary samples, we also classified mutated genes with various diseases, BPs, and MFs through cluster analysis. Notably, mutations in ALK and PTEN are concordant in a range of tumor types, including lung adenocarcinoma, endometrial cancer, colorectal cancer, and triple‐negative breast cancer [ 15 , 16 , 17 , 18 , 19 ]. Previously, a study examining clinically relevant mutations in 91 different malignancies also found mutation sites in anaplastic lymphoma kinase (ALK) and PTEN [ 20 ].…”
Section: Discussionmentioning
confidence: 99%